Green synthesis of silver nanoparticles by Kocuria flava isolated from photovoltaic panels for combating infections, cancer, and water pollution - Prajapati, Vishal; Panchal, Dhanusha; Dikshit, Manisha; Patel, Rajesh; Bhavsar, Sunil; Patel, Ashish; Sahoo, Dipak Kumar; Luhana, Kuldeep (Frontiers in Microbiology, 2025)
The extremophilic bacterial community associated with photovoltaic solar panels has demonstrated significant resilience to harsh environmental conditions such as desiccation, thermal fluctuations, and intense solar exposure. The bacterial strain Kocuria flava KKYHNGU1 was isolated from a PV panel and characterized for its resistance to alkaline pH (pH 9), salinity (1–9% w/v), UV radiation (approximately 8 min), and high temperatures (up to 55 °C). Bio-manufactured AgNPs from this isolate were characterized, including UV–visible spectroscopy (with wavelength peaks at 437 nm), FTIR, and X-ray diffraction, validating the crystalline configuration of the AgNPs, exhibiting intensity peaks at 28.02°, 32.46°, and 46.36°. The spherical shape and size (96 nm diameter) along with the silver content (87.06% w/w) of bio-synthesized AgNPs was confirmed through scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy. Metabolomic analysis through LC-MS revealed the presence of bioactive compounds possessing significant antimicrobial and anti-cancer properties, in addition to marked reduction capabilities. They have manifested notable antibacterial potential against Staphylococcus aureus with a 14 mm zone of inhibition and also proved effectiveness against Serratia marcescens, Bacillus cereus, and Escherichia coli. Additionally, the AgNPs effectively removed trimethoprim, achieving a 63.42% removal at 10 ppm within 120 min. These bio-fabricated AgNPs displayed remarkable anti-proliferative and pro-apoptotic activity against the THP-1 monocytic leukemia cell line, yielding an IC50 measurement of 40 μg/mL. These findings underscore the prospective applications of biogenic AgNPs in wastewater treatment and biomedical fields, illustrating their multiple functionalities.